Recent applications of the DP4+ method in the stereochemical elucidation of complex natural alkaloids (Research, Society and Development, 2025)
Stereochemical determination of natural compounds is essential for understanding their biological and pharmacological properties. The aim of this study is to present a narrative review in which recent studies (2021 to 2024) that used the DP4+ method to assign stereochemical configurations of natural alkaloids are presented and discussed. The DP4+ method proved to be highly effective in distinguishing between isomers with multiple chiral centers, even in complex structures. Furthermore, the reviewed compounds demonstrated a wide range of biological activities, reinforcing the importance of stereochemical rigor in natural product studies. DP4+ has established itself as an indispensable tool in natural product chemistry, especially when seeking to integrate structural rigor with pharmacological potential. Its application is expected to continue to grow in the coming years, especially with advances in simulation methods and statistical analysis.